Implementasi Metode Simple Additive Weighting (SAW) pada Sistem Pendukung Keputusan dalam Pemilihan Pegawai Terbaik - Kurnia, Ayu; Mirza, Ahmad Haidar; Suyanto, Suyanto; Rasmila, Rasmila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Employee performance appraisal is one of the efforts made by the company so that employees work well and produce high quality and dedicated employees. However, the assessment process that does not use assessment criteria and parameters is considered less objective because it assesses the subjectivity of each employee in the process of selecting the best employee. Decision Support System (SPK) is a decision-making process assisted by a computer system. The Simple Additive Weighting (SAW) method is one of the methods in SPK that can evaluate employees based on alternatives and criteria and predetermined weights. The SAW method can process large and unlimited amounts of data. SAW method only gives the maximum value or the highest value as the best. The calculation process using SAW on the selection of the best employee is based on five criteria, namely attendance, responsibility, initiative, teamwork, and compliance. This Decision Making System (SPK) uses the Python programming language which is implemented using Google Collaboratorry so that it can be used anywhere as long as it is connected to the internet.